MATURASI IKAN LELE MUTIARA Clarias gariepinus BETINA DENGAN ESTRADIOL-17? MELALUI PAKAN - Risa Febriyanti; Deny Sapto Chondro Utomo; Munti Sarida (Universitas Sriwijaya, 2021)
Some problems in catfish culture are the spawning circle, female catfish begin to mature gonad at 10 months, and after 1,5 months can spawn again. The purpose of this study was to evaluate the process of accelerating maturation female mutiara catfish with the addition Estradiol-17? by oral treatments. The study was design used 3 treatments : 0 ml/kg feed, 0,4 ml/kg feed, 0,6 ml/kg feed with three individual replications. The result showed that the addition of Estradiol-17? significantly affected on reproductive performance : Gonado Somatic Index (GSI) 102,3% and eggs diameter 16,4% in female mutiara catfish compared with 0 ml/kg feed. Key words : Clarias gariepinus, Eggs Diameter, Estradiol-17ß, Gonadosomatic Index (GSI), Reproductive Performance.